Synthesis and evaluation of heterocyclic pyrrolidene imines as optical chemosensors - Castro, Maria Cidália Rodrigues (2016)
Imine derivatives are an important class of compounds due their biological and optical properties making them suitable for several applications such as chemosensors, photochromic compounds, among others. In recent years the search for new colorimetric chemosensors for anions has been of great interest because of the role that ions play in chemical and biological processes. In this context and as part of an on-going research to develop efficient heterocyclic systems for photochromic and chemosensory applications, we report the synthesis, the photophysical characterization and the chemosensory ability of pyrrolidene heterocyclic imines functionalized with aryl or naphthyl moieties. Keywords: Imines,